ID: 43. Issue 1 (November 2015) - Donnelly, Raymond P.; Sheikh, Faruk; Dickensheets, Harold; Ramalingam, Thirumalai; Helming, Laura; Gordon, Siamon
<x xml:space="preserve">Abstract</x> Macrophages coexpress both the interleukin (IL)-2R-gamma chain (<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7p5k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives>c) and IL-13R-alpha 1. These receptor chains can heterodimerize with IL-4R<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pf0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> to form type I or type II IL-4 receptor complexes, respectively. We used macrophages derived from Il2rg and Il13ra1 knockout (KO) mice to evaluate the requirements for these receptor chains for induction of the alternative macrophage activation (AMA) pathway by IL-4 and IL-13. Absence of <alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7p5k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives>c significantly decreased activation of STAT6 by IL-4 but not IL-13. However, although activation of STAT6 by IL-4 was markedly reduced in Il2rg KO macrophages, it was not abolished, indicating that IL-4 can still signal through type II IL-4 receptors via the IL-13R<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pf0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>1 chain. IL-13 failed to activate STAT6 in macrophages derived from Il13ra1 KO mice; however, these cells remained fully responsive to IL-4. The inability of IL-13 but not IL-4 to signal in Il13ra1−/− macrophages correlated with the inability of IL-13 but not IL-4 to induce expression of genes such as Arg1, Retnla and Ccl11 that are characteristically expressed by alternatively activated macrophages. In addition, IL-13 but not IL-4 failed to induce membrane fusion and giant cell formation by Il13ra1 KO macrophages. These findings demonstrate that the IL-13R<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7pf0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>1 chain is essential for induction of the AMA pathway by IL-13 but not IL-4. Furthermore, the IL-13R-alpha 1 chain represents an excellent target for development of neutralizing monoclonal antibodies to inhibit the pro-inflammatory activities of IL-13.